Comparative Study of Understorey Birds Diversity Inhabiting Lowland Rainforest Virgin Jungle Reserve and Regenerated Forest - Ezyan Nor Hashim; Rosli Ramli (The Scientific World Journal, 2013)
A comparative study of understorey birds inhabiting different habitats, that is, virgin jungle reserve (VJR) and regenerated forest (RF), was conducted in Ulu Gombak Forest Reserve and Selangor and Triang Forest Reserve, Negeri Sembilan, Peninsular Malaysia. The objective of this study was to assess the diversity of understorey birds in both habitats and the effects of forest regeneration on the understorey bird community. The mist-netting method was used to capture understorey birds inhabiting both habitats in both locations. Species composition and feeding guild indicated that understorey bird populations were similar in the two habitats. However, the number of secondary forest species such as Little spiderhunter (Arachnothera longirostra) in VJR is increasing due to its proximity to RF. This study discovered that RFs in both study areas are not yet fully recovered. However, based on the range of species discovered, the RFs have conservation value and should be maintained because they harbour important forest species such as babblers and flycatchers. The assessment of the community structure of understorey birds in VJR and RF is important for forest management and conservation, especially where both habitats are intact.